Pendidikan agama Kristen dan budi pekerti kelas XI Pedoman Kehidupan / Ronald Kweniawan, Farida Fikri Widiastuti Yono, Dien Sumiyatiningsih - RONALD KWENIAWAN; Faridah Fikri Widiastuti Yono; Dien Sumiyatiningsih (Andi, 2014)
... jilid : ilus. ; 25 cm.